ENVIRONMENTALLY ORIENTED OPTIMIZATION OF SYNTHETIC DETERGENT FORMULATIONS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Synthetic detergents (SDs) are widely used in households and industry; however, traditional formulations pose a serious threat to the environment due to the poor biodegradability and toxicity of certain components. This article examines principles and practical approaches to environmentally oriented optimization of detergent composition, aimed at reducing the ecological impact while maintaining washing efficiency. Alternative surfactants, phosphate-free builders, and biodegradable additives are analyzed. A life cycle assessment (LCA)-based optimization methodology is proposed.